Parametric study on a conceptual badminton racket using finite element analysis - Fakhrizal Azmy Nasruddin, 1987-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2015